Are we too clean? A history and analysis of the hygiene hypothesis - Steed, Riley (My University, 2020)
Since the second half of the 20th century, the incidence of atopic disease has been on the rise. Allergies and rhinitis have become so common that some have called it an epidemic (Strachan, 1989). Initial research into the reasons for the rapid increase was done by David P Strachan, and he proposed the “hygiene hypothesis,” a theory claiming that early childhood infections can protect us against atopic diseases later in life (Strachan, 1989). Subsequent research found an interaction between T-helper 1 and T-helper 2 cells that, for many years, was considered to be the mechanism by which the hygiene hypothesis functioned (Romagnani, 1992). Eventually, it was discovered that this interaction did not work exactly as previously thought, and Graham A. Rook introduced a new theory to match the more recent research. Rook proposed the “old friends” hypothesis, which suggested that certain microbes, which evolved alongside humans, were responsible for protecting us against atopic disease (Rook et al., 2004). According to Rook, modern lifestyles have eliminated many of those microbes from our normal flora, and that explains the recent rise in atopic disease (Rook et al., 2004). The “old friends” hypothesis is now the prevalent atopic disease theory in epidemiology, and has helped improve both public and scientific understanding of the relationship between infection, hygiene, and atopy (Stiesma, et al., 2015).
Keywords: atopic diseases; old friends hypothesis